ELECTRICAL PROPERTIES OF MUNG BEANS (Vigna Radiata L.) - Novák, Ján (Journal on Processing and Energy in Agriculture, 2021)
This paper contains the results of measuring the electrical properties of mung beans (Vigna radiata L.) set. The conductivity and relative permittivity are the main parameters of dielectric material electrical properties. The electrical properties of mung beans samples had not been sufficiently measured, and the aim of this work was to perform the measurements of these properties. Measurements were performed under variable moisture content and the frequency of electric field from 0.1 kHz till 200 kHz for conductivity and in the range from 1 MHz to 16 MHz for relative permittivity, using RLC meter and Q meter, respectively. It was concluded that relative permittivity, and conductivity increased with increase of moisture content, resistivity, impedance, loss tangent, and relative permittivity decreased as the frequency of electric field increased, respectively.
Keywords: relative permittivity, electric resistance, conductivity, mung beans